Herramientas Google que apoyan a los procesos educativos - Yugcha Pazmiño, Marco Vinicio (2024)
The incorporation of Tics in education is a latent need; however, there are still teachers who do not use them due to ignorance especially of free tools. For this reason, the aim of this work was to analyze Google tools that can be used to support learning processes at the unified general baccalaureate level (UGB). This research was presented with a technological design, applied, bibliographical and descriptive. After conducting a bibliographic review and analysis of several Google tools, a proposal was designed to incorporate them into a class planning. The proposed proposal aims to be a starting point for teachers of unified general baccalaureate level or also called BGU to be able to adapt them at some point to their classes, in such a way that they bring their students closer to the new educational reality or trend that the world presents with respect to learning. It is recommended that teachers, in order to take effective advantage of this proposal, conduct ongoing training and updates, as well as analyze the particularities of their subjects.